2015
DOI: 10.1002/pssa.201532597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of composition‐graded interlayers in double‐heterostructure blue InGaN light‐emitting diodes

Abstract: The optical and electrical characteristics of the double‐heterostructure (DH) blue InGaN light‐emitting diodes (LEDs) with composition‐graded interlayers are studied numerically. Specifically, the detailed physical mechanisms and influences of grading layer thickness on the LED performance are explored systematically. Simulation results reveal that besides the advantages of mitigating lattice relaxation in real epitaxy, the employment of thick composition‐graded interlayers can benefit from the enhanced spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Experimental studies [6] showed that dislocation density could be reduced significantly by using linearly graded and step-graded AlGaN layers. A numerical study [7] also found the graded barrier layer could result in enhanced electron injection and confinement in double-heterostructure InGaN LEDs. On the other hand, the interface shape can affect the crossing of wave function envelops into the barrier layer, which changes the alloy disorder scattering and interface roughness scattering.…”
Section: Introductionmentioning
confidence: 95%
“…Experimental studies [6] showed that dislocation density could be reduced significantly by using linearly graded and step-graded AlGaN layers. A numerical study [7] also found the graded barrier layer could result in enhanced electron injection and confinement in double-heterostructure InGaN LEDs. On the other hand, the interface shape can affect the crossing of wave function envelops into the barrier layer, which changes the alloy disorder scattering and interface roughness scattering.…”
Section: Introductionmentioning
confidence: 95%
“…For example, in metal‐organic vapor phase epitaxy (MOVPE) step‐graded interlayers were shown to reduce the dislocation density of subsequent layers . Compositionally graded InGaN layers have also been shown to have an effect on the internal quantum efficiency improvement in double heterojunction blue light‐emitting diodes (LEDs) . Finally, it has been shown that thick, low‐temperature growth of compositionally graded InGaN helps to reduce defect formation and facilitates growth within the miscibility gap …”
Section: Introductionmentioning
confidence: 99%
“…[11] Compositionally graded InGaN layers have also been shown to have an effect on the internal quantum efficiency improvement in double heterojunction blue light-emitting diodes (LEDs). [12] Finally, it has been shown that thick, low-temperature growth of compositionally graded InGaN helps to reduce defect formation and facilitates growth within the miscibility gap. [13] However, high indium composition material still needs more attention.…”
Section: Introductionmentioning
confidence: 99%
“…where C is the Auger coefficient. Typical value of the Auger coefficient is from 10 -28 -10 -29 cm 6 /s for III-nitride semiconductors [38][39][40][41][42].…”
Section: Nonradiative Recombinationmentioning
confidence: 99%